Kegiatan Mencetak Dengan Pelepah Pisang untuk Mengembangkan Kemampuan Motorik Halus Anak Usia 5-6 di Taman Kanak-Kanak Dian Andalas - Faula Syahutri; Farida Mayar (Universitas Negeri Padang, 2022)
This study aims to describe the implementation of printing activities with banana stems for the development of fine motor skills in children, because the problem in developing fine motor skills in early childhood is that there is less variety of media used to develop fine motor skills in children. The purpose of this study was to determine the process of printing with banana stems to develop fine motor skills of children aged 5-6 years at Dian Andalas Kindergarten, Padang. This type of research is descriptive qualitative research. Data collection techniques used in the form of observation, interviews, and documentation. The data validity technique used is a data triangulation technique.The results of this study in general the activity of printing with banana stems to develop children's fine motor skills in Dian Andalas Kindergarten which was carried out by the teacher went well and as expected, because the teacher had designed learning activities according to the theme and sub-theme of the learning to be carried out. in the classroom. Evaluation of children's fine motor development can be done using several assessment techniques that are adapted to the curriculum such as assessment of work, checklists, anecdotal notes, daily assessments, monthly assessments, and semester assessments